Dinamika Aliran Nitrogen pada Fase Reproduktif Padi dalam Sistem Minapadi Berbasis Pakan Limbah Pertanian: Dynamics of Nitrogen Flow During the Reproductive Phase of Rice in a Rice-Fish Farming System Based on Agricultural Waste Feed - Nasrul, Muhammad; Rasyid, Burhanuddin; Abbas, Muh.; Saade, Edison; Marselianti (Universitas Hasanuddin, 2025)
Nitrogen use efficiency during the reproductive phase is critical for rice yield and grain quality. The rice-fish (minapadi) system that utilizes fish feed made from agricultural waste has the potential to enhance nitrogen availability through fish feces contribution. This study aimed to analyze the dynamics of nitrogen flow from soil to rice leaves and grains during the reproductive phase in a minapadi system. Four feed treatments were applied: no feed (N0), 5% Nitrogen (N1), 7% Nitrogen (N2), and 9% Nitrogen (N3). Nitrogen content was measured in soil, leaves, and grains during the primordia, flowering, and grain-filling stages. The results showed that N3 led to the highest nitrogen flow, with leaf N content reaching 3.1% and grain N content at 1.47%. This system demonstrates improved nutrient efficiency through the synergy between fish and rice, promoting sustainable agriculture based on local resources.